2002
DOI: 10.1099/0022-1317-51-10-851
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Helicobacter pylori vacA, cagA and iceA genotypes in Nigerian patients with duodenal ulcer disease

Abstract: Distinct virulence factors of Helicobacter pylori have been associated with clinical outcome of the infection; however, considerable variations have been reported from different geographic regions. Data on genotypes of African H. pylori isolates are sparse. The aim of this study was to determine the prevalence of specific genotypes of H. pylori in Nigerian patients with duodenal ulcer and non-ulcer dyspepsia. H. pylori was cultured from endoscopic biopsies obtained from 41 Nigerian patients (19 with duodenal u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
35
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 12 publications
(14 reference statements)
10
35
4
Order By: Relevance
“…The pattern of vacA alleles in this study is in agreement with those reported in other studies (3,8,16,18,20). However, the frequency of vacA s1/m1 allelic type in this study is higher than figures reported from The Netherlands (36%), Hong Kong (26 to 31%), and Nigeria (24%), but lower than figures reported from Brazil (80%) and Korea (78%) (3,11,16,20,21). In the present investigation, the rare vacA s2/m1 allele was detected in 4 (2%) of the 246 gastric biopsy specimens examined, also reported in studies in South Africa and Chile (12,13).…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…The pattern of vacA alleles in this study is in agreement with those reported in other studies (3,8,16,18,20). However, the frequency of vacA s1/m1 allelic type in this study is higher than figures reported from The Netherlands (36%), Hong Kong (26 to 31%), and Nigeria (24%), but lower than figures reported from Brazil (80%) and Korea (78%) (3,11,16,20,21). In the present investigation, the rare vacA s2/m1 allele was detected in 4 (2%) of the 246 gastric biopsy specimens examined, also reported in studies in South Africa and Chile (12,13).…”
Section: Resultssupporting
confidence: 83%
“…The vacA genotypes s1/m1, s1/m2, s2/m2, and s2/m1 were found in 48, 28, 9, and 2% of the specimens, respectively (Table 1), whereas, 15 biopsy specimens (6%) were incomplete and thus did not yield a detectable PCR product for the vacA s or m regions. The pattern of vacA alleles in this study is in agreement with those reported in other studies (3,8,16,18,20). However, the frequency of vacA s1/m1 allelic type in this study is higher than figures reported from The Netherlands (36%), Hong Kong (26 to 31%), and Nigeria (24%), but lower than figures reported from Brazil (80%) and Korea (78%) (3,11,16,20,21).…”
Section: Resultscontrasting
confidence: 46%
See 1 more Smart Citation
“…Likewise Van doorn et al announced that isolates with iceA1 are more leading to ulcerative diseases (14). In contrast with Smith et al study that detected the iceA gene in all of the H.pylori isolates from Nigerian patients; we detected the iceA1 gene in only 22.2% and the iceA2 gene in 54% of our cases, but in accordance to our study they detect no association between the iceA1 allele and peptic ulcer disease (22).…”
Section: Discussioncontrasting
confidence: 57%
“…The prevalence of type I H. pylori in patients with DU was observed to be significantly higher than in patients with G/GU (94.3% and 78.6%, respectively; P ϭ 0.004) ( Table 2). In a great amount of research, the prevalence of type I H. pylori was reported to vary among different countries, regions, and patient groups, and it was reported as 68% in England (21), 78 to 80% in Turkey (5,15), 80% in Belgium (11), 82% in Brazil (1), 82% in Japan (17), 93% in Nigeria (16), and 97% in China (24). The majority of those studies (1,5,11,17,21) indicated that in patients with DU, the cagA positivity rate is relatively higher than in patients with gastritis or GU and ranges from 80 to 100%.…”
mentioning
confidence: 99%